Analytical and environmental chemistry in the framework of risk assessment and management: The lagoon of Venice as a case study - Pojana, G.; Critto, A.; Micheletti, C.; Carlon, C.; Busetti, Francesco; Marcomini, A. (NEW SWISS CHEMICAL SOC, C/O NOVARTIS AG, K-25 1 45, CH-4002 BASEL, SWITZERLAND, 2003)
Prevention of toxic pollutant discharge and remediation of contaminated sediments and soils aretopics increasingly addressed by the scientific community and the stakeholders. The research activity carried out on the lagoon of Venice highlights the crucial role played by analytical and environmental chemistry in assessing the environmental behavior of chemicals (i.e. occurrence level, transformation, ultimate fate) and exposure of human and environmental targets to pollutants. The extrapolation from analytical data to decisional steps was accomplished by data treatment (descriptive and multivariate statistics, spatial statistics), environmental modeling (e.g. partitioning bioaccumulation models and linear regression models), environmental risk assessment (ERA), and a GIS-based Decision Support System (DSS). Results obtained by this integrated approach supported analytical and environmental chemistry by improving the selection of priority pollutants, optimizing sampling design, and identifying critical environmental pathways. Both uncertainty minimization and cost saving of the overall decision process could be achieved. Selected results are presented here on the application of the proposed approach to the contaminated sediments of the lagoon of Venice and to the brownfield of the Porto Marghera industrial district.Both well-known persistent pollutants (e.g. polychlorinated dioxins/furans (PCDD/Fs), polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), metals and metalloids, and aromatic surfactants and their metabolites), as well as new classes of pollutants (e.g. endocrine disrupting compounds, EDCs) were investigated. The analytical data indicated that the most persistent and toxic organic and inorganic chemicals were found mainly in bottom sediments (especially those near the Porto Marghera industrial district), while substances such as surfactantsand their metabolites and EDCs occurred mainly in water and were redistributed over the whole lagoon. Exposure characterization allowed Environmental Risk Assessment (ERA) to be undertaken, including the estimation of risk for both human and environmental health. The ERA procedure, developed according to a tiered approach, was applied to contaminated soils of the Porto Marghera industrial district. The ecological risk associated with contaminated lagoon sediments for the benthic community and aquatic food web was also assessed, resulting in a significant risk posed especially by mercury, cadmium and PAHs. Finally, a risk-based decision support system (DSS) for the rehabilitation of the Porto Marghera contaminated site was developed, which included environmental risk and remediation technologies.